Code-Switching and Code-Mixing in Bilingual Learning: A Sosiolinguistic Case Study at SMP 4 Widodaren - Erlindya Permani Putri; Yunus Sulistyono (Universitas Muhammadiyah Surakarta, 2025)
The purpose of this study is to determine the form and function of code switching and code mixing in the learning process, especially in English and Javanese subjects. This study examines the use of language, especially in class VII at SMP Negeri 4 Widodaren. This type of research uses descriptive qualitative research. The data in this study are in the form of transcribed recordings, then classified according to the form, function and type of code switching and code mixing. The results of this study are that in English subjects, fifteen data on the use of internal code mixing were found, three data on the use of external code mixing, three internal code switching, and three external code switching. In Javanese subjects, two internal code mixing and three external code mixing were found. Another finding of this study is that there are implications of the use of code switching and code mixing in English and Javanese subjects that can be seen from pedagogical, linguistic, and socio-cultural perspectives. It is concluded that the implementation of bilingual learning, especially in English and Javanese subjects, influences the occurrence of code switching and code mixing in students.